2014
DOI: 10.1534/genetics.113.158824
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Function of the Glucanosyltransferase Gas1 in the DNA Damage Response Linked to Histone H3 Acetyltransferases in Saccharomyces cerevisiae

Abstract: Chromatin organization and structure are crucial for transcriptional regulation, DNA replication, and damage repair. Although initially characterized in remodeling cell wall glucans, the b-1,3-glucanosyltransferase Gas1 was recently discovered to regulate transcriptional silencing in a manner separable from its activity at the cell wall. However, the function of Gas1 in modulating chromatin remains largely unexplored. Our genetic characterization revealed that GAS1 had critical interactions with genes encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…3, top). Intriguingly, Sas3 was reported to interact genetically with Gas1, a ␤-1,3-glucanosyltransferase recently shown to regulate gene silencing, in the DNA damage response pathway (47). Dele- tion of GAS1 resulted in defects in checkpoint activation upon DNA damage.…”
Section: Roles Of Kat6 Hats In Cell Cycle Regulation and Stem Cell Mamentioning
confidence: 99%
“…3, top). Intriguingly, Sas3 was reported to interact genetically with Gas1, a ␤-1,3-glucanosyltransferase recently shown to regulate gene silencing, in the DNA damage response pathway (47). Dele- tion of GAS1 resulted in defects in checkpoint activation upon DNA damage.…”
Section: Roles Of Kat6 Hats In Cell Cycle Regulation and Stem Cell Mamentioning
confidence: 99%
“…Another important possibility is that the unglycosylated proteins caused by Gas1p dysfunction should be accumulated, potentially impairing proteome maintenance, causing constitutively ER stress responses, and possibly resulting in UPR-mediated cell death. In addition, Gas1p deficiency causes broad DNA damage sensitivity and defective cell cycle checkpoint activation, which cause a phenotype resembling premature ageing [8, 20]. Consistent with this observation, Gas1p disruption has previously been shown to reduce growth rates by approximately 25%, while fivefold Gas1p overexpression was not observed to affect cell growth parameters and cell wall properties [21].…”
Section: Resultsmentioning
confidence: 75%
“…For example, the loss of Gas1p activity results in swollen, more spherical cells and causes defects in cell wall assembly that decrease cell viability and enhance cell sensitivity to heat and cell wall-disrupting compounds such as Congo red [6]. On the other hand, Gas1 deficiency results in broad DNA damage sensitivity and defects in telomeric silencing, which is involved in regulating senescence [7, 8]. Therefore, the different locations of Gas1p in yeast cells should determine its diverse functions.…”
Section: Introductionmentioning
confidence: 99%
“…In budding yeast, cells lacking Gas1 have weakened and abnormal cell walls and are sensitive to cell wall-perturbing drugs. Recently, however, a surprising new role for Gas1 activity has been identified in the regulation of transcriptional silencing at rDNA loci ( Eustice and Pillus, 2014 ; Ha et al , 2014 ; Koch and Pillus, 2009 ). In particular, it has been suggested that Gas1 physically interacts with Sir2, an nicotinamide adenine dinucleotide (NAD) + -dependent histone deacetylase that is a subunit of the rDNA silencing complex (RENT: regulator of nucleolar silencing and telophase exit), to repress Pol II-dependent transcription at the rDNA locus ( Huang and Moazed, 2003 ).…”
Section: Resultsmentioning
confidence: 99%